"Girl power gone wrong": #MeToo, Aziz Ansari, and media reporting of (grey area) sexual violence. Issue 5 (3rd July 2020) - Hindes, Sophie; Fileborn, Bianca
ABSTRACT: Sexual violence has predominantly been discursively constructed as bounded and binary, leaving little room for ambiguous or uncertain experiences. The #MeToo movement, however, saw some highly contested cases enter into mainstream news coverage that challenged these dominant understandings, including the divisive case of Aziz Ansari. This research uses a post-structural feminist framework to examine Australian news media reporting of this case in order to understand how discourses around sexual violence and sexual consent are (re)produced by news media following the #MeToo movement. The study found that whilst some discourse was more nuanced, the majority of reporting still perpetuated limited and binary understandings of sexual violence. Much reporting constructed pressure and coercion as the normal and acceptable "reality" of (hetero)sex, failing to acknowledge coercion as potentially harmful and problematic, as well as failing to consider the possibilities for doing consent differently. Reporting also (re)produced narrow and stereotypical understandings of gender roles, with women primarily seen as bearing the onus of gatekeeping sexual experiences, and men seen as "naturally" aggressive pursuers of sex. Ultimately, we argue that news media works as a site of erasure for particular forms and experiences of sexual violence.